Analisa Shakemap dan Jenis Sesar Studi Kasus: Gempa bumi Terasa di Purworejo – Jawa Tengah - Nugroho Budi Wibowo; Dian Susri Nurhaci (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Earthquake July 18, 2016 at 5:59:00 am occur on land 18 Km Northwest Purworejo. The earthquake measuring 3.6SR at a depth of 13 kilometers and was felt in Purworejo I - II MMI. This study aims to analyze the earthquake affected based on shakemap analysis and determine the type of fault used the initial motion of P waves that recorded on seismograph. Shakemap analysis using shakemap application at BMKG servers based on the accelerograph network BMKG. Meanwhile, an analysis the type of fault using focal application with data input signals from the seismograph SeisComP3 system. The highest values of peak ground acceleration (PGA) recorded in BPBD Kebumen’s station is 0.5075 gal (EW component), 0.5018 gal (NS component) and 0.3538 gal (UD component). Model shakemap for Purworejo earthquake felt I SIG (I-II MMI) in Purworejo, Kebumen and Banjarnegara. The models of focal mechanism are the first nodal obtained strike 321, dip 33, rake 95, and the second nodal obtained strike 135, dip 57, rake 87. Based on the distribution model compression axis (up or T) and dilatation (down or P), the type of fault is reverse fault. The epicenter of the Purworejo earthquake correlated with the Rebung faultin Purworejo.Keyword: Shakemap, Focal Mechanism, PGA, Intensity, Earthquake, Fault.